2020
DOI: 10.1002/pssb.201900589
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Characterization of Nitrogen‐Polar AlGaN/AlN Heterostructure for High‐Electron‐Mobility Transistor

Abstract: A nitrogen‐polar (N‐polar) AlGaN/AlN high‐electron‐mobility transistor (HEMT) is proposed, and the generation of a 2D electron gas (2DEG) is simulated. The band diagram of N‐polar (Al)GaN/AlN shows the generation of the 2DEG, whereas that of the conventional metal‐polar (Al)GaN/AlN structure shows the generation of a 2D hole gas. Furthermore, the concentration of the 2DEG is considerably high even when the (Al)GaN layer is as thin as a few nanometers. N‐polar AlGaN/AlN is grown on sapphire substrates with a mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…It provides a very useful method to obtain high-crystalline-quality N-polar AlN, which is very difficult for the in situ epitaxial growth techniques. [11][12][13][14][15][16][17][18][19][20][21][22] direction of AlN films after HTA process, showing the polarity inversion region. Reprinted from [80].…”
Section: High Temperature Annealing (Hta)mentioning
confidence: 98%
See 1 more Smart Citation
“…It provides a very useful method to obtain high-crystalline-quality N-polar AlN, which is very difficult for the in situ epitaxial growth techniques. [11][12][13][14][15][16][17][18][19][20][21][22] direction of AlN films after HTA process, showing the polarity inversion region. Reprinted from [80].…”
Section: High Temperature Annealing (Hta)mentioning
confidence: 98%
“…The polarities of AlN include Al-polarity (+c-polarity) and N-polarity (−c-polarity). Except for some special applications such as lateral polarity structure (LPS) and N-polar high electron mobility transistors (HEMTs) [21,22], N-polar AlN is not desired because of its poor crystalline quality, surface morphology, and chemical stability. Ronny Kirste et al demonstrated the surface of N-polar AlN was dominated by a typical columnar morphology, with an average width of ~500 nm and a height difference of ~100 nm [23], as shown in Figure 1.…”
Section: Polarity Control Of Aln/sapphire Templatementioning
confidence: 99%
“…By using a flow-rate-modulation technology with an interruption time of 4 s to grow the low temperature (LT )-GaN nucleation layer, the crystalline quality of the N-polar GaN was significantly improved [11]. The sapphire substrate with a misorientation angle of 2.0° was reported to be useful to grow the N-polar AlGaN film [12]. The growth of N-polar AlN layer with flow-modulation technology was also conducted, and the full width at half maximum (FWHM) values of 72 and 1,020 arcsec were attained for (002) and (100) XRD diffractions, respectively [13].…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] The N-polar GaN/AlGaN structures are attracting interest due to the AlGaN back-barrier effect and several promising results being reported. [7][8][9][10] Higher-frequency operation requires a substrate with high resistivity and breakdown voltage. Thus, semi-insulating Fe-doped GaN substrates are frequently used.…”
Section: Introductionmentioning
confidence: 99%
“…To improve the performance of AlGaN/GaN HEMTs, an aluminum nitride (AlN) interlayer is used between AlGaN and GaN because the alloy scattering can be suppressed due to AlN/GaN structure, and the electron mobility can be improved . The N‐polar GaN/AlGaN structures are attracting interest due to the AlGaN back‐barrier effect and several promising results being reported . Higher‐frequency operation requires a substrate with high resistivity and breakdown voltage.…”
Section: Introductionmentioning
confidence: 99%